2008
DOI: 10.1007/s10029-008-0437-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-traumatic lateral abdominal wall hernia

Abstract: A rare lateral abdominal wall hernia is described in an adult patient. This was diagnosed in a patient with a prominent right lateral abdominal wall deformity. The patient had been experiencing pain that increased progressively in severity over time. A computerized tomography (CT) scan of the abdomen revealed the location of the lateral abdominal wall defect. The hernia defect was through the transversus abdominis and the internal oblique, with the inferior aspect of the 11th rib forming part of the superior b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In the literature, to our knowledge, Castillo-Sang et al [ 2 ] only reported a similar type of hernia like the present case. They reported a 56-year-old male who presented a right lateral abdominal wall bulge in the midaxillary line immediately below the rib cage.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In the literature, to our knowledge, Castillo-Sang et al [ 2 ] only reported a similar type of hernia like the present case. They reported a 56-year-old male who presented a right lateral abdominal wall bulge in the midaxillary line immediately below the rib cage.…”
Section: Discussionsupporting
confidence: 64%
“…Nonincisional lateral abdominal wall hernia (LAWH) is a very rare condition, although incisional hernias along the lateral abdominal wall incision can occur infrequently [ 1 , 2 ]. LAWH has to be differentiated from other rare types of hernias such as lumbar hernia or spigelian hernia.…”
Section: Introductionmentioning
confidence: 99%
“…There are several classifications for abdominal hernias: non-traumatic LAWH, congenital lateral abdominal defect, and traumatic LAWH. 1 The LAWH described here was an unusual type of hernia. Castillo-Sang and colleagues 1 reported the first case of a LAWH in a 56-year-old male in 2008.…”
Section: Discussionmentioning
confidence: 82%
“…Hernias of the lateral abdominal wall have been reported only in adult patients, describing its location in the axillary midline just below the rib cage.…”
Section: Discussionmentioning
confidence: 99%